Prenatal care: missed opportunity for HBV prevention in women of childbearing age in rural Senegal. (13th November 2019) - Djaogol, T; Coste, M; Marcellin, F; Diallo, A; Carrieri, P; Boyer, S; ,
Abstract: Background: Perinatal transmission of hepatitis B virus (HBV) constitutes an important risk in highly endemic countries including Senegal. Although the prevalence of chronic HBV infection is estimated at 11% in this country, specific data on women of childbearing age are sorely lacking. We described in this study the prevalence of the HBV antigen (HbsAg) in women of childbearing age in rural Senegal, as well as general knowledge on HBV and hepatitis B status awareness. Methods: A cross-sectional study including HBV screening was conducted at home in the rural Niakhar area. Chronic HBV infection was determined through HBsAg detection using dried blood spots. Socio-demographic and behavioral data were collected through standardized face-to-face questionnaires. The analyzes included 368 women aged 15-49 (67% married; 65% with at least 1 child) enrolled from October 2018 to March 2019. Results: Preliminary results show that 49 women (13%) had positive HBsAg. Only 68 women (18%) have already heard about HBV. Among them, 53% knew that there exists an HBV vaccine and 78%, 75% and 67% correctly answered that HBV can be transmitted through blood contact, childbirth and sexual intercourse, respectively. Among the 233 (63%) women who had already given birth, 76% had attended at least 4 antenatal care sessions and 74% had given birth in a healthcare facility for their last pregnancy. However, only 1% reported to have already been screened for HBV. Main reasons reported for not having been screened were having never heard about this test (80%) and not having been offered screening during antenatal care sessions (10%). Conclusions: General knowledge and awareness of HBV status are particularly low in women of childbearing age living in rural Senegal, despite high antenatal care sessions attendance. Given the high prevalence of chronic HBV infection found in this population, it is urgent to ensure systematic HVB screening and to provide adequate information to women during pregnancy. Key messages: The prevalence of chronic HBV is high in women of childbearing age in Senegal. National recommendations for women attending antenatal care sessions should include HBV screening and counselling.